PROFIL ORIENTASI DAN GAYA BERKONFLIK SISWA SMP DAN SMA SEKOLAH LENTERA HARAPAN DI CURUG, TANGERANG DAN BANJAR AGUNG, LAMPUNG - Nasution, Elyzabeth Bonethe; Tambunan, Edwin M.B.; Lenjau Lung, Firman Daud (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Sekolah Lentera Harapan Curug and Banjar Agung are located within a certain religion-dominated society. Both schools are also situated in societies that are economically, socially, and culturally transforming due to geographic locations; Curug is close to a metropolitan city, and Banjar Agung is near a suburb. Hence, both schools, along with the students must be able to wisely respond to the economic, religious, and ethnic differences that surround them to prevent conflict. To equip the schools and the students, Youth & Peace Project team from IR UPH conducted a peace and conflict resolution workshop for the students in both schools. Aside from giving a 9-modules workshop, the team also established profiling for two crucial aspects: orientation to conflict and natural conflict styles. The pre-test and post-test results for orientation to conflict, as well as the conflict styles, assert the close relations between the knowledge that students obtained during the workshop with their natural conflict styles. Students tended not to solely rely on their natural conflict styles anymore. This confirmed that the intervention, in the form of a workshop, was impactful for students. One of the factors that supported the intervention was the lessons and values students acquired in the schools.